Game of thrones 4 : a feast for crows - Martin, George R. R. (London : Harper Voyager, 2014)
HBO's hit series A GAME OF THRONES is based on George R R Martin's internationally bestselling series A SONG OF ICE AND FIRE, the greatest fantasy epic of the modern age. A FEAST FOR CROWS is the fourth volume in the series. 'Fantasy fiction's equivalent to THE WIRE' Telegraph.
Keywords: Seven kingdoms (Imaginary place) -- Fiction